Kemampuan Dekomposisi Pajak Tangguhan untuk Memprediksikan Arus Kas - Rachmawati, Dyna (Jurnal Akuntansi Kontemporer, 2010)
This study uses two models to test the predictive ability of deferred taxes. The first model tests the predictive ability of deferred tax assets and deferred tax liabilities. The second model tests the predictive ability of decomposition of deferred tax assets and deferred tax liability. There are various results of the predictive ability of decomposition of deferred tm liabilities. Depreciation and amortization is not cash flows predictor. Capital lease and other temporary differences are statistically significant towards cash flows. It means that they are cash flows predictor.